Immunoglobulin M and immunoglobulin G repertoire sequencing data of two donors first infected with SARS-CoV-2 then vaccinated with mRNA-1273 - Chernyshev, Mark; Sakharkar, Mrunal; I. Connor, Ruth; Dugan, Haley L.; Sheward, Daniel J.; Rappazzo, C. Garrett; Stålmarck, Aron; Forsell, Mattias M.N.; F. Wright, Peter; Corcoran, Martin; Murrell, Ben; M. Walker, Laura; et al. (Karolinska Institutet, 2023)
Immunoglobulin M (IgM) and immunoglobulin G (IgG) repertoire sequencing libraries from two donors who were first infected by index SARS-CoV-2, then vaccinated by the mRNA-1273 vaccine. We acquired longitudinal peripheral blood mononuclear cells (PBMCs) samples from each respective donor as follows: 11 or 14 days post-infection (acute timepoint), 32 or 37 days post-infection (convalescent timepoint), 160 or 169 days post-infection (pre-vax timepoint), and 9 or 7 days post-vaccination (post-vax timepoint). Three IgM libraries were generated from each donor for the Acute timepoint, as well as one IgG library per timepoint per donor for a total of 6 IgM and 6 IgG Rep-seq libraries.
Keywords: Immunogenetics (incl. genetic immunology); Medical and Health Sciences; Medicin och hälsovetenskap; Immunology; Immunologi